Rare forms of diabetes in children and adolescents - Małecki, Maciej T.; Klupa, Tomasz (Przewodnik Lekarza/Guide for GPs, 2006)
Most of diabetes cases diagnosed in pediatric patients represent typical autoimmune type 1 diabetes. However, more and more cases of monogenic form of disease (neonatal diabetes, mitochondrial diabetes, MODY) are being diagnosed in children and adolescents. The proper differential diagnosis is critical for the choice of treatment, predicting progress of disease in affected individuals, and defining the prognosis in the family. In this paper, the etiology of non-type 1 diabetes in children and adolescence will be reviewed. The clinical aspects of management of the affected individuals will be discussed.